Icomat 2013
DOI: 10.1002/9781118803592.ch19
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Activated Martensite: Its Relationship to Non-Thermally Activated (Athermal) Martensite

Abstract: The classification of martensitic displacive transformations into athermal, isothermal or anisothermal is discussed. Athermal does not mean "no temperature dependence" as is often thought, but is best considered to be short for the notion of no thermal activation. Processes with no thermal activation do not depend on time, as there is no need to wait for sufficient statistical fluctuations in some specific order parameter to overcome an activation barrier to initiate the process. Clearly, this kind of process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Villa et al 28 observed isothermal martensite kinetics on the isochronal cooling a Fe-Cr-Ni-Cu alloy which was attributed to thermally activated growth of athermal nucleated lath martensite. Laughlin et al 29 generalized the discussion of thermally-activated stages in the martensite transformation curve by considering the relative position of the M S temperature and the nose of the thermal-activated martensite transformation, and the imposed cooling rate. Here we provide evidence that the intergrain autocatalysis in polycrystalline Fe-31wt%Ni-0.02wt%C is controlled by a thermally activated process.…”
Section: Discussionmentioning
confidence: 99%
“…Villa et al 28 observed isothermal martensite kinetics on the isochronal cooling a Fe-Cr-Ni-Cu alloy which was attributed to thermally activated growth of athermal nucleated lath martensite. Laughlin et al 29 generalized the discussion of thermally-activated stages in the martensite transformation curve by considering the relative position of the M S temperature and the nose of the thermal-activated martensite transformation, and the imposed cooling rate. Here we provide evidence that the intergrain autocatalysis in polycrystalline Fe-31wt%Ni-0.02wt%C is controlled by a thermally activated process.…”
Section: Discussionmentioning
confidence: 99%
“…Anisothermal martensitic transformations are thermally activated transformations on continuous cooling. 40 Martensitic phase formation depends upon the alloy composition and rate of cooling. As the solute content increases in Ti alloy, the martensitic start temperature (M s ) and martensitic finish temperature (M f ) decrease, as illustrated in Figure 7.…”
Section: Martensitic Phasesmentioning
confidence: 99%
“…The martensite transformation curve has been descri bed by empirical equations whose coefficients referred to the steel composition, thermodynamic properties, and the austenite grain size [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, the relationship between microstructure and the volume fraction of martensite transformed still deserves consideration.…”
Section: Introductionmentioning
confidence: 99%